A comprehensive analysis of the genomic and proteomic profiles of a megalocytivirus isolated from Larimichthys crocea - Liu, Xiaodong; Chi, Hongshu; Yang, Xixi; Zheng, Zaiyu; Zhu, Chunhua; Wu, Yunkun; Chang, Wei-Jen; Gong, Hui (Frontiers in Microbiology, 2025)
IntroductionThe prevalence of viral diseases has posed significant challenges to the sustainable development of large yellow croaker (Larimichthys crocea) aquaculture, with megalocytivirus being one of the primary viral pathogens affecting this species. There have been two proteomic and genomic studies regarding two members of the genus Megalocytivirus: the spotted knifejaw iridovirus (SKIV) and the infectious spleen and kidney necrosis virus (ISKNV). However, both studies were conducted more than 10 years ago. To further investigate the pathogenesis of megalocytivirus, we sequenced the genome of the viral strain FD201807 isolated from L. crocea, and conducted a proteomics analysis.MethodsViral DNA was sequenced using the Illumina HiSeq 2000 platform. Viral proteins from purified virions and supernatants of viral infected cells were subjected to LC-MS/MS analysis, and the expression of four viral proteins was further confirmed by Western blotting. The entire viral genome was subjected to phylogenetic and bioinformatic analyses.ResultsThe FD201807 genome comprises 112,214 bp of double-stranded DNA with a G + C content of 53.53%. It contains 130 potential open reading frames, with coding capacities ranging from 41 to 1,293 amino acids. Phylogenetic analysis of the whole-genome sequence indicated that the closest known megalocytivirus related to FD201807 is Pompano iridovirus, with a sequence identity of 98.98%. Label-free proteomics analysis identified 27 viral proteins in the viral-infected cell culture supernatants and 46 viral proteins in the purified virus of FD201807. Among these, 19 viral proteins were detected in both the viral-infected cell culture supernatants and the purified virus samples, while 8 viral proteins were exclusively identified in the viral-infected cell culture supernatants. Notably, there were two proteins derived from the cultured cell line MFF-1 (mandarin fish fry cell line-1), namely cytochrome c and ubiquitin-activating enzyme E1, present in both the purified virus samples and the culture supernatant of infected cells. These cellular proteins may be associated with virus-host protein interactions and/or host cell apoptosis.DiscussionWe present the most comprehensive proteomic analysis to date of the megalocytivirus isolated from L. crocea, and help identify highly expressed proteins that may serve as future targets for immunotherapy and biochemical analysis.